2014
DOI: 10.1177/0898010114531856
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Support Spirituality in Health Care Communication

Abstract: All health care professionals benefit from proficiency in spiritual communication skills. Attention to spiritual concerns ultimately improves care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Spirituality is not something anyone could be compelled to and requires a certain convergence in communication. If relation-centred care is always already spiritual as Reblin et al note (Reblin et al 2014 , p. 269), the caregivers and volunteers of our study have been well prepared. This applies to the institution of hospices we came upon.…”
Section: Discussionmentioning
confidence: 61%
“…Spirituality is not something anyone could be compelled to and requires a certain convergence in communication. If relation-centred care is always already spiritual as Reblin et al note (Reblin et al 2014 , p. 269), the caregivers and volunteers of our study have been well prepared. This applies to the institution of hospices we came upon.…”
Section: Discussionmentioning
confidence: 61%
“…It is possible that nurses are somewhat uncomfortable or feel less effective discussing spiritual matters (Molzahn & Sheilds, 2008; Reblin et al, 2014). It is also possible that other hospice team members such as chaplains or the family’s spiritual advisors engage in these conversations with patients and caregivers, and as such nurses feel that they can focus on different caregiver and patient needs.…”
Section: Discussionmentioning
confidence: 99%
“…If requested by caregivers or deemed appropriate by the hospice nurse, engaging in spiritual discussions for those with and without prior religious affiliation can be accomplished by asking about family traditions and providing conversational “space” that allows the caregiver to explain and discuss religious and/or cultural practices, thus providing more holistic end of life care (Reblin et al, 2014). …”
Section: Implications For Nursingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are also researchers who state that research on hope-raising strategies provides evidence of hope and satisfaction in life but that there is limited evidence that it reduces psychological stress. Besides, there is insufficient evidence of what can be done to implement hope-building strategies [8]. In 2001, Kaye Herth developed a package called Hope Intervention Program (HIP) that aims to increase hope [11], where it has been shown that it is possible to produce and maintain hope with appropriate methodology.…”
Section: Introductionmentioning
confidence: 99%